Ecological correlates of extinction risk in Chinese amphibians. Issue 10 (15th July 2019) - Chen, Chuanwu; Chen, Cangsong; Wang, Yanping
Abstract: Aim: China is one of the countries with the richest amphibian biodiversity in the world. Among the 408 Chinese amphibians, 174 species are considered threatened according to the China Biodiversity Red List in 2015. However, to date, which species traits or extrinsic factors are correlated with extinction risk in Chinese amphibians is rarely examined. The aims of this study were thus to identify the patterns and correlates of extinction risk in Chinese amphibians and to determine whether patterns and processes are similar between species with either small or large geographic distributions. Location: China. Methods: We obtained twelve species traits and four extrinsic factors that have been commonly linked to the extinction risk of amphibians. After phylogenetic correction, these factors were tested separately and in combination to identify their correlations with extinction risk in all Chinese amphibians, and in small‐ranged and large‐ranged species. Results: Geographic range size and elevational range were the most important predictors of extinction risk in all Chinese amphibians. Although extinction risk in small‐ranged amphibians was predominantly determined by small elevational range, in large‐ranged amphibians it was driven by geographic and elevational ranges, body size, human exploitation index and adult microhabitat. Small‐ranged amphibians had a higher percentage of threatened species than large‐ranged species. However, the body size distributions were not statistically different between these two amphibian subgroups. Main conclusions: Our findings suggest that conservation priority should be given to species with small geographic and elevational ranges. Small‐ranged and large‐ranged amphibians should be conserved with different strategies because the factors influencing extinction risk differ between these two groups. In specific, the reduction of habitat loss should be a primary focus of management efforts because species with small geographic and elevational ranges are particually vulnerable to habitat loss. Conservation efforts should also focus on protecting large‐bodied species and preventing human overexploitation for the effective conservation of large‐ranged amphibians.